Analysis of Solar Radiation Shielding in Space for Climate Mitigations of the Earth - Kyung Bae Jang; Tae Ho Woo (Energy Science & Engineering)
ABSTRACT Solar radiation modification (SRM) through space solar shielding is a proposed strategy to mitigate global warming. This approach involves reflecting sunlight back into space while allowing Earth's infrared radiation to escape, thereby controlling climate change. The effectiveness of space solar shielding is evaluated using a complex algorithm that considers various parameters of the shielding satellite, such as its size, orbit, and deployment mechanism. The thickness of the shield should be similar to the solar wavelength, around 400‐600 nm, to deflect sunlight with an expected mass density lower than 1.5 g/m2. The primary objective is to reduce the greenhouse effect by mitigating the increase in atmospheric carbon dioxide (CO2) levels. In 2022, CO2 levels in the United States surpassed the pre‐industrial level of 278 ppm, increasing by approximately 7.11 ppm due to the consumption of coal, natural gas, and petroleum for electricity generation. This point reflects the relatively recovered climate environment at the end of the pandemic. Therefore, long‐wavelength solar radiation energy going out from the Earth is absorbed and increases the temperature of the Earth's atmosphere, so we want to reduce the solar energy coming into the Earth. The performance of space solar shielding is analyzed using a system dynamics (SD) model, which incorporates feedback loops and non‐linear relationships between various variables. The results indicate that while the effectiveness of CO2 reduction may diminish over time, the overall climate mitigation benefits could be significant. However, the large scale of space solar shielding raises concerns about potential side effects. Further research is necessary to assess the environmental and socio‐economic implications of this geoengineering approach.